PENGEMBANGAN BUKU PENGAYAAN KETERAMPILAN MEMBACA BAHASA INDONESIA YANG BERMUATAN NILAI KEWIRAUSAHAAN (Universitas Negeri Semarang, 2013)
One of language skills students need to master and improve is reading skill. The reading skill is respective skill functioning to enrich the knowledge. A good reading resource for the students is the reading resource that contains educative values. One of educative values students need to have is entrepreneurship. Teaching material for reading skill in the form of enrichment book is integrated with entrepreneurship values. The research and development method employed in this research is referred to Borg and Gall theory. The research results suggested the tendency of needs from either teacher or students. Those ideas were managed as the development principals of the reading skill enrichment book containing entrepreneurship values. Afterwards, those principals were managed as the basis of the arrangement of the reading skill enrichment book. The result of expert assessment towards the enrichment book indicated that it is good and suitable to use as teaching material. Seeing the expert assessment and effectiveness test, the reading skill enrichment book containing the entrepreneurship values that was arranged is good and suitable to use as the learning media in improving reading skill as well as entrepreneurship values